Hybrid repair of thoracoabdominal aneurysm: An alternative strategy for preventing major complications in high risk patients. (15th November 2018) - Di Marco, Luca; Murana, Giacomo; Leone, Alessandro; Alfonsi, Jacopo; Mariani, Carlo; Cefarelli, Mariano; Pantaleo, Antonio; Pacini, Davide; Di Bartolomeo, Roberto
Abstract: Background: Nowadays, less invasive endovascular procedures have been employed in high risk patients for thoracoabdominal aortic aneurysm (TAAA) in order to try to reduce the risk of major complications. The aim of the study was to analyze the results of our hybrid 2-stage approach for TAAA repair. Methods: Between July 2011 and September 2016, 17 consecutive high-risk patients received a hybrid 2-stage procedure for TAAA repair. Mean age of the population was 58.9 ± 9.0 years and 16 (94.1%) were male. Of them, 7 (41.2%) suffered of chronic obstructive pulmonary disease and 15 (88.2%) had a previous history of aortic operation. Three patients had Marfan syndrome (17.6%). The preoperative anatomy of the aneurysms was classified according to "Crawford classification" in type II (n = 6, 35.3%), type III (n = 10, 58.8%) and type IV (n = 1, 5.9%). All patients were followed up with an angio CT-scan at 1, 3 months and yearly thereafter. Results: In-hospital mortality was 11.8% (2 patient). None of the patients experienced paraplegia and paraparesis. Major post-operative complications were pancreatitis 17.6% (3/17). At follow-up (mean time of 23.3 ± 21.7 months) 2 patient died (12.5%) waiting for the second stage endovascular completion. Median interval time between the 2 steps was 35 days. Overall survival at 1- and 3-years was 75.6 ± 1.0. One type Ib and 1 type III endoleak were noted and successfully treated with an additional stent graft. Conclusions: The results of hybrid 2-stage TAAA repair on high-risk patients are satisfactory and therefore encouraging. The extremely low incidence of spinal cord injury could make this technique the technique of choice for this type of pathology in selected high-risk patients. At follow-up, residual endoleaks occur although surgical reoperations are not often needed. Highlights: Less invasive endovascular procedures have been employ to treat thoracoabdominal aortic aneurysm in order to reduce the risk of major complications. The aim of the study was to analyze the results the hybrid 2-stage approach for extensive thoracoabdominal aneurysm repair. Since 2011, 17 consecutive high-risk patients received this hybrid treatment and then were followed-up with seriated angio CT-scan. In-hospital mortality was 11.8% (2 patient) and none of the patients experienced paraplegia and paraparesis. At follow-up, residual endoleaks are observed although surgical reoperations are not often needed.